Development of IPAS on Matter and its Changes Based on PjBL to Improve the Science Process Skills for Grade E Vocational High School - Exsa Rahmah Novianti; Hardeli (Jurnal Penelitian Pendidikan IPA, 2024)
The aim study to produce module of IPAS learning based on project based learning to improve the science process skill for grade E SMK and to determine level of validity practicality and effectiveness. The type of research used research and development (R&D). The development model used 4D models (define, design, development and dessiminate). The module of IPAS learning was validated by three chemistry lecturers from FMIPA UNP and two chemistry teachers from SMK Swasta Bakti Agro Mandiri and SMKN 1 Kempas. Determination of the practicality level of module IPAS learning by two chemistry teachers from SMK Swasta Bakti Agro Mandiri and SMKN 1 Kempas and 30 students of grade E SMK Swasta Bakti Agro Mandiri. The results of the practicality analysis based on teacher and student response questionnaires obtained Aiken scores of 0.97 and 0.93 respectively in the very high practicality category. Therefore, it can be said that the module based on project based learning to improve the science process skill for grade E SMK on matter and its change material is valid, practicable, and effective.